Implementation Of Augmented Reality At State Polytechnic Of Samarinda Building Using Marker Based Tracking Method - Sianipar Yosephine Yulietayanti Natalia; M. F. Andrijasa; Rheo Malani (Politeknik Negeri Indramayu, 2022)
Augmented Reality (AR) is increasingly used in the industrial revolution 4.0 as it is today, one of which is as a medium for information and learning. Currently, the Samarinda State Polytechnic (POLNES) is one of the universities located in Samarinda and has buildings as a place for lecture activities. The campus introduction media used today is to use miniatures and this is still not effective in providing the right information results. The research with the title